Dynamic modelling of cell death during biofilm development - Fagerlind, Magnus G. (2013)
Biofilms are currently recognised as the predominant bacterial life-style and it has been suggested that biofilm development is influenced by a number of different processes such as adhesion, detachment, mass transport, quorum sensing, cell death and active dispersal. One of the least understood processes and its effects on biofilm development is cell death. However, experimental studies suggest that bacterial death is an important process during biofilm development and many studies show a relationship between cell death and dispersal in microbial biofilms. We present a model of the process of cell death during biofilm development, with a particular focus on the spatial localisation of cell death or cell damage. Three rules governing cell death or cell damage were evaluated which compared the effects of starvation, damage accumulation, and viability during biofilm development and were also used to design laboratory based experiments to test the model. Results from model simulations show that actively growing biofilms develop steep nutrient gradients within the interior of the biofilm that affect neighbouring microcolonies resulting in cell death and detachment. Two of the rules indicated that high substrate concentrations lead to accelerated cell death, in contrast to the third rule, based on the accumulation of damage, which predicted earlier cell death for biofilms grown with low substrate concentrations. Comparison of the modelling results with experimental results suggests that cell death is favoured under low nutrient conditions and that the accumulation of damage may be the main cause of cell death during biofilm development.